(untitled) (Journal of Biomedical Investigation, 2024)
Background: Load porterage is a blue-collar job that is more manually driven in low-and-middle income countries where individuals are prone to sustain musculoskeletal complications due to exposure to risks such as carrying heavy loads for shoppers. Aim: This study aimed to investigate the prevalence and pattern of work-related musculoskeletal disorders (WMSDs) among load porters in Bodija and Akande markets in Ibadan, Oyo State. Materials and Methods: This cross-sectional study was conducted using consecutive sampling technique in selecting 113 load porters with the market conveniently selected. The Nordic Musculoskeletal Questionnaire (NMQ) was used to assess the prevalence and pattern of WMSDs. Descriptive statistics of mean, frequency and percentage were used to summarize the data. Results: One hundred and two (90.27%) participants reported musculoskeletal pain in one or more body parts in the last 12 months with low back (68.14%) and neck (66.37%) as the most affected body regions. There was significant association between prevalence and tribe and BMI (p=0.04 and p=0.05 respectively). Fifty-two (46.02%) participants reported pain in the last 7 days with low back (36.28%) and neck (33.63%) as the most affected regions. Conclusion: There was high prevalence of WMSDs among respondents. The most affected body regions were low back and neck. Recommendation: It was therefore, recommended that healthcare providers should embark on awareness campaign to educate and enlighten load carriers on proper lifting technique which will enhance good work hygiene and ergonomic practice among load carriers.